A unifying framework for transparency optimized controller design in multilateral teleoperation with time delays. (December 2021) - Tumerdem, Ugur; Yilmaz, Nural
Abstract: Multilateral teleoperation is an umbrella term for various N -robot haptic teleoperation schemes and contains bilateral teleoperation as a special case with N = 2 . While transparency of bilateral teleoperation systems can be analyzed through hybrid matrices and transparent controllers can be designed with four channel/Lawrence architectures, such a general analysis and design framework has not yet been established for multilateral teleoperation systems. Here, a framework is proposed to achieve transparency in multi-user shared control multilateral teleoperation systems even in the presence of time delays. First, a novel control law unifying a wide range of dominance factor, control and communication architectures is proposed. This control law enables the adaptation of all bilateral linear Lawrence architectures to multilateral teleoperation. Second, a novel transparency analysis approach is proposed and it is shown that TOPF architecture is the only Lawrence architecture that can potentially achieve ideal transparency in multilateral teleoperation under time delays. Third, based on proposed L 2 stability criteria, a trade-off between stability robustness and transparency under varying time delays is demonstrated. Effectiveness of the proposed framework is validated with numerical analyses and experiments.